Influence Of Yarn Count & Micron On The Dyeability Of Woven Wool Fabrics Dyed With Acid Jacquard Dyes (International Journal of Environmental Sciences, 2025)
This work aimed to specify if there is any relation between yarn count, fiber fineness, and rate of dye up take on fabrics during the dyeing process. Worsted woven wool fabrics in different yarn counts;(30/2,40/2,50/2,60/2,70/2)metric and different fineness;(17.08 -23.25) were dyed via acid Jacquard dye to investigate this relation.The dyeing variables were studied to achieve the optimum dye uptake which were achieved via 2% of acid Jacquard Dyein acedic media (pH 3) at high temp. (90 °C) for 1 hr. Then the fabrics in different yarn counts and fineness were dyed in the optimum conditions to examine their color strength to record their Impact on the fabric dyeability and its mechanical properties. Count 60/2 with a fineness of 21.50 micron,recorded the highest color intensity whereas count 40/2 with a fineness of 21.23 micron,recorded the lowest color intensity. The highest tensile strength results for woolen fabrics from 30/2 to 40/2 metric yarn were achieved using filaments with a spinning fineness of (18.09 to 17.08) microns, respectively. These filaments were considered to be fine-diameter filaments with small length.